2019
DOI: 10.1122/1.5049136
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling the rheology of thixotropic elasto-visco-plastic materials

Abstract: To describe the macroscopic rheological behavior of thixotropic elasto-visco-plastic (TEVP) materials, phenomena that take place in their microstructure must be accounted for. To this end, we couple the tensorial constitutive model by Saramito for EVP materials with thixotropy, extending the ideas of isotropic hardening, and with kinematic hardening (KH), to account for back stresses. We use a scalar variable that describes the level of structure at any instance and a modified Armstrong–Frederick KH equation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 82 publications
0
37
0
Order By: Relevance
“…Thus, the yield strain of the Pluronic solution is found to be « y = 0.016. As shown by Varchanis et al (21) and can be seen in Fig. 1 D and E, the SRM/HB model predicts a linear elastic solid response in the linear regime (γ 0 → 0), something that does not hold for the Pluronic solution.…”
Section: Significancementioning
confidence: 78%
“…Thus, the yield strain of the Pluronic solution is found to be « y = 0.016. As shown by Varchanis et al (21) and can be seen in Fig. 1 D and E, the SRM/HB model predicts a linear elastic solid response in the linear regime (γ 0 → 0), something that does not hold for the Pluronic solution.…”
Section: Significancementioning
confidence: 78%
“…Most of the blood constitutive modelling investigations do not present the normal stress prediction, and hence we are not able to make a comparison with other findings. Varchanis et al [62] in their work reported a significant contribution of normal stress in simple shear tests and compared their findings with those predicted by the ML-IKH model, which was found to have similar behavior. The presence of normal stresses is suspensions is attributed the intense interaction between the particles.…”
Section: Unitsmentioning
confidence: 88%
“…In this work, we modified the constitutive law for blood flow modeling, introducing a thixotropic elasto-viscoplastic formulation. The proposed model was based on the formulation of Varchanis et al [62], which incorporated thixotropy, elasticity and viscoplasticity following an additive elastoplastic decomposition. It was able to capture all the essential steady and transient experimental data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations